A review on environmental factors regulating arsenic methylation in humans - Tseng, Chin-Hsiao (Toxicology and applied pharmacology, 2009)
Subjects exposed to arsenic show significant inter-individual variation in urinary patterns of arsenic metabolites but insignificant day-to-day intra-individual variation. The inter-individual variation in arsenic methylation can be partly responsible for the variation in susceptibility to arsenic toxicity. Wide inter-ethnic variation and family correlation in urinary arsenic profile suggest a genetic effect on arsenic metabolism. In this paper the environmental factors affecting arsenic metabolism are reviewed. Methylation capacity might reduce with increasing dosage of arsenic exposure. Furthermore, women, especially at pregnancy, have better methylation capacity than their men counterparts, probably due to the effect of estrogen. Children might have better methylation capacity than adults and age shows inconsistent relevance in adults. Smoking and alcohol consumption might be associated with a poorer methylation capacity. Nutritional status is important in the methylation capacity and folate may facilitate the methylation and excretion of arsenic. Besides, general health conditions and medications might influence the arsenic methylation capacity; and technical problems can cause biased estimates. The consumption of seafood, seaweed, rice and other food with high arsenic contents and the extent of cooking and arsenic-containing water used in food preparation may also interfere with the presentation of the urinary arsenic profile. Future studies are necessary to clarify the effects of the various arsenic metabolites including the trivalent methylated forms on the development of arsenic-induced human diseases with the consideration of the effects of confounding factors and the interactions with other effect modifiers.